Vascular healing after kissing balloon inflation: Nine-month 3D optical coherence tomography analysis in corelab. (June 2022) - Yamawaki, Masahiro; Okamura, Takayuki; Nagoshi, Ryoji; Fujimura, Tatsuhiro; Murasato, Yoshinobu; Ono, Shiro; Serikawa, Takeshi; Hikichi, Yutaka; Norita, Hiroaki; Nakao, Fumiaki; Sakamoto, Tomohiro; Shinke, Toshiro; et al.
Abstract: Background: The jailing strut configuration with link-free and distal guidewire recrossing (LFD) at the side branch orifice (SBO) reduces incomplete stent apposition (ISA) after kissing balloon technique (KBT) in crossover stenting of coronary bifurcation lesions (CBLs). However, data regarding vascular healing after KBT are lacking. We investigated vascular healing 9 months after crossover stenting followed by KBT with optical coherence tomography (OCT) guidance in a prospective multicenter registry. Methods: Fifty-nine patients with CBLs (LFD, 35 patients; non-LFD, 24 patients) were studied. The jailing configuration of the SB and the wire-recrossing position, incidence of ISA and uncovered struts, and neointima unevenness score (NUS) in the main vessel (MV) after 9 months were determined by off-line 3D-OCT in the core laboratory. Results: The ISA rate was significantly higher at the SB ostium and distal MV after KBT in the non-LFD group, compared to the LFD group. After 9 months, incidence of ISA (18.3 ± 18.2 vs. 6.0 ± 8.7%, p < 0.01) and uncovered struts (8.7 ± 9.9 vs. 4.7 ± 7.3 %, p = 0.08) were higher at the SB ostium with higher SB restenosis in the non-LFD group. In distal MV, NUS was significantly higher (3.1 ± 1.1 vs. 2.5 ± 0.6, p < 0.05). In true-CBLs, an increase in uncovered struts and ISA rate was prominent in the proximal MV and opposite SB. No differences were observed in the 9-month clinical outcomes. Conclusion: Visualization of the wire recrossing point and the SB-jailing strut pattern by OCT plays an important role to optimize the KBT in CBL stenting, resulting in favorable mid-term vascular healing.